Readability and suitability of English digital patients' education materials related to medications, which are available on three health information websites in Malaysia / Siti Nurul Fathihah Baharudin - Baharudin, Siti Nurul Fathihah (2015)
Aim: Digital or web based materials are currently broadly utilized to enhance the effectiveness of patients' education to improve accessibility, and relatively lowers the publication cost. The efficacy of such materials however may be compromised if they cannot be read or comprehended by the audience. Hence, readability and suitability are literacy tools intended to evaluate the appropriateness of written materials regardless of being printed or in digital forms. In Malaysia, the readability and suitability of Patients Education Materials were never assessed. Hence, this study aimed to evaluate on the readability and suitability of PEMs in Malaysia. Method: English digital patients' education materials (PEMs) downloaded from three websites www.knowyourmedicine.gov.mv, www.bpfk.gov.my, www.myhealth. gov.my. The PEMs were evaluated in terms of readability level by using Simple Measure of Gobbledygook (SMOG), Flesch Kincaid Grade Level (FKGL) and Flesch Reading Ease (FRE). The PEMS suitability levels were evaluated by using Suitability Assessment of Material (SAM) score sheets. Results: The websites www.myhealth.gov.my had the highest median readability level of 13.91 and 13.17 for SMOG and FKGL respectively while FRE score was 33%. This is followed by the website www.bpfk.gov.my with median SMOG and FKGL11.29 scores of 12.35, FRE score of 43.91. www.myhealth.gov.my. 21 (52.5%) out of the 40 PEMs evaluated with SAM score sheet were categorized as suitable. Conclusion: PEMs available on the three websites were written in high readability level. Significant difference can be seen between readability scores between all three websites. Majority of PEMs available on the three websites may be classified as suitable and adequate in terms of suitability.